Root architecture development in stony soils. Issue 4 (11th June 2021) - Morandage, Shehan; Vanderborght, Jan; Zörner, Mirjam; Cai, Gaochao; Leitner, Daniel; Vereecken, Harry; Schnepf, Andrea
Abstract: Soils with high stone content represent a challenge to root development, as each stone is an obstacle to root growth. A high stone content also affects soil properties such as temperature or water content, which in turn affects root growth. We investigated the effects of all soil properties combined on root development in the field using both experiments and modeling. Field experiments were carried out in rhizotron facilities during two consecutive growing seasons (wheat [ Triticum aestivum L.] and maize [ Zea mays L.]) in silty loam soils with high (>50%) and low (<4%) stone contents. We extended the CPlantBox root architecture model to explicitly consider the presence of stones and simulated root growth on the plot scale over the whole vegetation period. We found that a linear increase of stone content resulted in a linear decrease of rooting depth across all stone contents and developmental stages considered, whereas rooting depth was only sensitive to cracks below a certain crack density and at earlier growth stages. Moreover, the impact of precipitation‐influenced soil strength had a relatively stronger impact on simulated root arrival curves during the vegetation periods than soil temperature. Resulting differences between stony and non‐stony soil of otherwise the same crop and weather conditions show similar trends as the differences observed in the rhizotron facilities. The combined belowground effects resulted in differences in characteristic root system measures of up to 48%. In future work, comparison of absolute values will require including shoot effects—in particular, different carbon availabilities. Core Ideas: We present a dynamic root architecture model that considers macroscopic soil properties. Root elongation rate and preferred growth direction are influenced by stones. We simulate the effects of soil properties on root architecture development using field data. Only belowground effects are considered by the root architecture model. Similar trends in measured and simulated root growth are observed in two different soils.